ETIOLOGY, PATHOGENESIS AND CLINICAL DIAGNOSIS OF PEYRONIE’S DISEASE - Шатылко, Тарас Валерьевич; Попков, Владимир Михайлович; Королев, Александр Юрьевич; Крылова, Олеся Владимировна (Medicine in Kuzbass, 2017)
Peyronie’s disease remains an understudied progressing disease being  one of the relevant problems of modern urology and andrology. This condition may cause erectile dysfunction in men of fertile age and its negative impact on sexual function adversely affects patients’ quality of life. This article reviews epidemiology, pathophysiology and specifics of recording history and clinical diagnosis of Peyronie’s disease, that includes questionnaires, physical examination, evaluation of erectile function and penile deformity.
Keywords: Peyronie’s disease; penis; fibroplastic induration; fibrous plaque; erectile dysfunction; tunica albuginea